2019
DOI: 10.1002/aoc.5103
|View full text |Cite
|
Sign up to set email alerts
|

Application of biosynthesized palladium nanoparticles (Pd NPs) on Rosa caninafruit extract‐modified graphene oxide as heterogeneous nanocatalyst for cyanation of aryl halides

Abstract: A green palladium (Pd)‐based catalyst supported on Rosa canina fruit extract‐modified graphene oxide [Pd nanoparticles (NPs)/reduced graphene oxide (RGO)‐Rosa canina] hybrid materials has been used as a recoverable and heterogeneous nanocatalyst for cyanating aryl halides using K4[Fe (CN)6] as the resource of cyanide. The nitriles were achieved in good to high yield, and the catalyst can be recovered and reused for up to seven cycles with no remarkable decrease in its catalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 70 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…Hemmati et al [ 128 ] demonstrated cyanation of aryl halides using K 4 [Fe(CN) 6 ] as a source of cyanide in the presence of palladium (Pd)‐based catalyst supported on Rosa canina fruit extract‐modified GO (PdNPs/RGO) with Na 2 CO 3 and DMF at 120°C for 2–12 h. The authors examined various solvents and bases for this reaction. DMF as solvent and Na 2 CO 3 gave excellent yields (96%) in a short reaction time.…”
Section: Go‐supported Metals As Catalystmentioning
confidence: 99%
“…Hemmati et al [ 128 ] demonstrated cyanation of aryl halides using K 4 [Fe(CN) 6 ] as a source of cyanide in the presence of palladium (Pd)‐based catalyst supported on Rosa canina fruit extract‐modified GO (PdNPs/RGO) with Na 2 CO 3 and DMF at 120°C for 2–12 h. The authors examined various solvents and bases for this reaction. DMF as solvent and Na 2 CO 3 gave excellent yields (96%) in a short reaction time.…”
Section: Go‐supported Metals As Catalystmentioning
confidence: 99%
“…Traditional methods for synthesis of aryl nitriles include Rosenmund-von Braun [29,30] and Sandmeyer [31][32][33][34][35] reactions which have drawbacks of using stoichiometric CuCN at harsh reaction conditions. To overcome these disadvantages, nowadays nucleophilic cyanation of aryl halides was performed using transition metals such as Pd [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50], Ni [51] and Cu [52,53] under efficient conditions. Among the different solids for preparation of recyclable catalysts, organic polymers [54] having unique properties such as easy preparation steps, tunable hydrophilic-hydrophobic character and high loading of desired functional group are excellent materials for depositing metal nanoparticles [55].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this plant extract also allowed the green synthesis of hybrid organometallic nanomaterials like palladium nanoparticles supported on graphene oxide. 33,34 All these synthesis methods used other reactants or pH adjusting and were carried at temperatures ranging from 60 to 100 C. Pulit and Banach investigated the effect of metal salt concentration, reaction pH and temperature to the nanoparticle formation. 28 The smallest nanoparticles (silver with 47.44 nm and gold with 17.24 nm average size) were synthesized at pH 12.…”
Section: Introductionmentioning
confidence: 99%